Design of Polarization-independent Optical Power Splitter based on Si/SiNx Double-layer Waveguide - Hai-guang LIU; Yue-teng ZHANG; Yu-chen SONG; Han-xiao SHEN; He-ming CHEN; Jing-li WANG (Guangtongxin yanjiu, 2022)
Aiming at the problems that most polarization-independent optical power splitters have complex structure and high loss, a polarization-independent 1×2 power splitter based on Si/SiNx double-layer waveguide is designed in this paper, which is used for equally splitting 1 550 nm optical signals. The refractive index of SiNx material can be adjusted by the Plasma Enhanced Chemical Vapor Deposition (PECVD) . The beat lengths of Transverse Electric (TE) polarization mode and Transverse Magnetic (TM) polarization mode is equal, and the polarization independent function is realized. Meanwhile, the device size is reduced by selecting the width of the multimode interference waveguide. And the insertion loss and reflection loss are further reduced by optimizing the taper waveguide. The 3D finite-difference time-domain method is used for modeling and simulation. The results show that the size of the proposed optical power splitter is only 3.0μm×16.8μm, and the insertion loss, reflection loss and splitting ratio are as low as 0.04 and-48.80 dB, and 1.000 33, respectively. The bandwidth can reach 380 nm with insertion loss less than 1 dB, which has potential application value in the future integrated optical path.